Effect of Use of Productive Zakat, Work Ethos and Mustahiq Empowerment on The Growth of Mustahiq Micro Business in DKI Jakarta - Hendriyanto, Hendriyanto; Mariati Tamba, Mariati Tamba; Tri Suratmi, Tri Suratmi (LPPM Universitas Respati Indonesia, 2023)
The Baitul Maal Bank Rakyat Indonesia Foundation (YBM BRI) was established in 2001 and was inaugurated as an Amil Zakat Institution (LAZ) in 2002. LAZ YBM BRI is a Philanthropic Institution that manages Zakat, Infaq, Alms and Endowments Funds which are carried out in a professional manner. YBM BRI is committed to improving the quality of life and vertical mobility of poor families through a series of economic empowerment programs.LAZ YBM BRI provides micro business capital assistance from zakat funds to mustahiq. This study intends to determine the effect of utilization of productive zakat, work ethic and mustahiq empowerment on the growth of mustahiq micro enterprises. The method in this study used quantitative methods, data were collected by filling out questionnaires using a sampling technique by 100 respondents. The data analyst used in this research is Multiple Linear Regression Analysis. From calculations using SPSS, this study resulted in the following conclusions. First, that the variable utilization of productive zakat influences the growth of micro-enterprises in Jakarta. Second, that the mustahiq work ethic variable has no effect on the growth of mustahiq micro businesses in Jakarta. Third, that mustahiq empowerment affects the growth of mustahiq micro businesses in Jakarta. Fourth, the utilization of zakat, mustahiq work ethic and mustahiq empowerment simultaneously influence the growth of mustahiq micro businesses in Jakarta. Keywords: Micro business growth, Utilization of productive zakat, work ethic, empowerment of mustahiq